The Effect of Employee Empowerment and Job Satisfaction on Intention to Stay in Nigeria Banking Industry: A Case Study of Guaranty Trust Bank - Oluwaseun, Ibrahim Shukura (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
This paper is investigating the influence of employees’ empowerment and job satisfaction on their intention to stay using a sample from a Bank in Lagos, Nigeria. Employees’ feeling of empowerment and their job satisfaction were measured using 5-items each. Intention to stay was measured using 4-items. Empowered employees are expected to less likely to quit and also expected to have higher job satisfaction. Consequently, we believe that increased job satisfaction is the reason that empowered employees may not quit their jobs. Our outcomes show a positively significant relationship that exists between employee’s empowerment and job satisfaction also employee empowerment has a positive association with intention to stay, intention to stay is explained by job satisfaction and job satisfaction act as a mediator between employee empowerment and intention to stay. Keywords: employees’ empowerment and job satisfaction on intention to stay.

ÖZ: Bu çalışmanın amacı çalışanların güçlendirilmesinin ve iş tatminlerinin işten ayrılmama niyeti üzerindeki etkisini incelemektir. Çalışmada Lagos state, Nijerya faaliyet gösteren bir devlet bankası çalışanlarından ver toplanmıştır. Çalışanların güçlendirilen dair algıları ve iş tatmin düzeyleri beşer sorudan oluşan ölçeklerle ölçülmüştür. İşlen ayrılmama niyeti ise dört soruluk bir ölçek ile belirlenmiştir. Güçlendirilen çalışanların işten ayrılma niyetinin daha düşük olması beklenmektedir. Güçlendirilen çalışanların aynı zamanda iş tatminleri de yüksek olacaktır. Bununla bağlantılı olarak güçlendirilme iş tatmini artırdığı için güçlendirilme çalışanların ayrılma niyeti azalmakta olduğuna inanıyoruz. Çalışmanın sonuçları çalışanların güçlendirilmesi ile iş tatmini arasında pozitif bir ilişki olduğunu teyit etmekte, çalışanların güçlendirilmesi ile işten ayrılmama niyeti arasında da bir pozitif ilişki ve işten ayrılma ile iş tatmini arasında da bir pozitif ilişki olduğunu göstermektedir. İş tatmini bir aracı değişken olarak çalışanların güçlendirilme ve çalışanların işten ayrılmama niyetini etkilemektedir. Anahtar Kelimeler: niyetini çalışanların, güçlendirme ve iş tatmini kalmak.
Master of Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2016. Supervisor: Prof. Dr. Cem Tanova.
Keywords: Business Administration; Employee motivation - Banking Industry - Nigeria; Banks and Banking - Employee empowerment; employees’ empowerment and job satisfaction on intention to stay